Time series analysis on crime solution efficiency in the province of Tarlac - Barcayan, Jeanniel I. (PSU Urdaneta Campus Research Journal, 2015)
The crime solution efficiency revealed an upward trend while the annual monthly crime rate showed a downward trend. This was a good indication that for the past seven year, the Tarlac Provincial Office managed to lower the crime incidence and elevate their performance on crime solution. Also, the time trend for homicide, rape, carnapping, and cattle rustling sloped upward while the time trend for homicide, physical, injury, theft, robbery and index crime incidnce as a whole sloped downward. he estimated model for crime solution efficiency in the province of Tarlac was a seasonal ARIMA (0,1,1). The model was used to forecast the monthly series for the next three years.